Broad geographical circulation of a novel vesiculovirus in bats in the Mediterranean region - Luo, Dong-Sheng; Harazim, Markéta; Maufrais, Corinne; Bonas, Simon; Martinkova, Natalia; Lalis, Aude; Nakouné, Emmanuel; Adjogoua, Edgard Valéry; Douno, Mory; Kadjo, Blaise; López-Roig, Marc; Pikula, Jiri; et al. (PLOS Neglected Tropical Diseases, 2025)
Author summary Bats are the natural hosts for a wide variety of viruses, particularly those belonging to the family Rhabdoviridae, which include the lyssaviruses, the etiological agents of rabies. This viral family is one of the most abundant and diverse, with 434 officially recognized species. However, the current diversity of these viruses in bats remains poorly understood. To address this, we developed a new method for detecting rhabdoviruses in bat samples collected over a period of 12 years in several European and African countries. From nearly 2,000 samples, we discovered a new rhabdovirus, which was named Mediterranean bat virus (MBV). MBV has been detected in the blood and oral swabs of specific bat species (Rhinolophus sp. and Miniopterus schreibersii) living on both sides of the Mediterranean region. Based on phylogenetic analysis, we determined that MBV represented a unique group within the genus Vesiculovirus, but still related to other bat vesiculoviruses discovered in China and North America. These results expand the host range and viral diversity of bat rhabdoviruses, and pave the way for further studies to determine the transmission route and dissemination dynamics of these viruses in bat colonies, as well as to assess their potential threat to public health.